Effect of Light Colour, Timing, and Duration of Light Exposure on the Hatchability of Artemia Spp. (Branchiopoda: Anostraca) Eggs. Issue 4 (1st July 2016) - El-Magsodi, Mohamed Omar; Bossier, Peter; Sorgeloos, Patrick; Van Stappen, Gilbert
Abstract: We investigated the effect of illumination on the hatching of eggs of one strain of Artemia franciscana Kellogg, 1906 and two strains of parthenogenetic Artemia (Branchiopoda, Anostraca). The following light parameters were used: colour (red, blue, and white light, having different intensities in the range $22{\rm{ - }}27\;μ {\rm{mol}}\;{\rm{E}}/{{\rm{m}}^2}$ per s, corresponding with different wavelengths in the range $400-700\;{\rm{nm}}$ ), and additionally (Experiment 1) duration of light exposure (varying between 15 min and continuous light) or (Experiment 2) timing of light exposure (from the 1 st to the 13 th hour of incubation of eggs for hatching). Continuous darkness was included as negative control. Hatching percentage was determined after 24 and $48\;{\rm{h}}$, and additionally after $72\;{\rm{h}}$ in Experiment 2. For all samples a relatively short exposure to light $(6\;{\rm{h}}\;{\rm{or\;less}})$ during the initial hours of incubation maximally triggered the hatching process; $1\;{\rm{h}}$ of light had highest efficiency when given during the 4 th hour of incubation of eggs for hatching, and less so when supplied earlier or later. Lower sensitivity was observed for the red light spectral region $(600-700\;{\rm{nm}})$, with mostly limited differences between blue $(400-500\;{\rm{nm}})$ and white $(400-700\;{\rm{nm}})$ light. Differences between samples could be linked to factors such as chorion thickness, pigmentation, storage conditions, diapause status and genotypic differences in general, but to what extent each of these factors contributes to the variability among the strains needs to be studied by analysing a more comprehensive set of samples. The fact that the inter-strain differences observed in our study were only of quantitative nature nevertheless suggests that light triggers hatching in Artemia eggs through a process that is consistent throughout the genus. Our work could contribute to a better understanding of the hatching biology of dormant life stages in Crustacea in general.